2022
DOI: 10.1002/marc.202200650
|View full text |Cite
|
Sign up to set email alerts
|

Azo‐Functionalized Thermoplastic Polyurethane for Light‐Driven Shape Memory Materials

Abstract: Shape memory polymers have great potential in the fields of soft robotics, injectable medical devices, and as essential materials for advanced electronic devices. Herein, light-triggered shape-memory thermoplastic polyurethane (TPU) is reported using azido TPU grafted by the photoswitchable azo compound. The trans-cis transitions of the azobenzene on the side chain of the TPU induce the recoiling of the main chain, leading to shaping memory behavior. Under UV irradiation, cis-azo allows the oriented main chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Preparation of SP-Siloxy-Terminated PGT via the GT Method: PET was first synthesized as previously described; [47,[54][55][56][57] MC (270 g), 1,4butanediol (18.55 mL), and BF3•THF (1.746 mL) were added to the reaction vessel under anhydrous conditions at 25 °C. After thoroughly mixing, 118 g of ECH and 92 g of THF 92 g were transferred to a dropping funnel.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of SP-Siloxy-Terminated PGT via the GT Method: PET was first synthesized as previously described; [47,[54][55][56][57] MC (270 g), 1,4butanediol (18.55 mL), and BF3•THF (1.746 mL) were added to the reaction vessel under anhydrous conditions at 25 °C. After thoroughly mixing, 118 g of ECH and 92 g of THF 92 g were transferred to a dropping funnel.…”
Section: Methodsmentioning
confidence: 99%
“…It can prepare structures with high flexibility, excellent processing and molding capabilities, and other characteristics, and is gaining more and more attention as a flexible material for uses such as wearable devices, 14,15 energy-absorbing structures, 2,16,17 and medical materials. [18][19][20] In recent years, flexible polymer SLS, represented by TPU, have gradually emerged. 21 Xu et al tested the mechanical properties of dumbbell-type structure specimens printed by SLS technique with different build orientations (XYZ) and different mixing ratios using a mixture ratio of old and new TPU powders, and the results showed that the new powder had better particle quality and thermal properties and was more effective for SLS processing, while TPU specimens printed in planar and edge orientations had similar excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoplastic polyurethane (TPU) is a semicrystalline polymer between plastic and rubber with good water resistance, ductility, as well as excellent biocompatibility and wear resistance, 7–13 where TPU composites are divided into hard segment molecular chains and soft segment molecular chains, where the hard segment determines the strength of the material and the soft segment determines the toughness of the material. It can prepare structures with high flexibility, excellent processing and molding capabilities, and other characteristics, and is gaining more and more attention as a flexible material for uses such as wearable devices, 14,15 energy‐absorbing structures, 2,16,17 and medical materials 18–20 …”
Section: Introductionmentioning
confidence: 99%